Reaching a Different Population of MSM in West Africa With the Integration of PrEP Into a Comprehensive Prevention Package (CohMSM-PrEP ANRS 12369—Expertise France). (1st November 2020) - Eubanks, August; Dembélé Keita, Bintou; Anoma, Camille; Dah, Ter T.E.; Mensah, Ephrem; Maradan, Gwenaëlle; Bourrelly, Michel; Mora, Marion; Riegel, Lucas; Rojas Castro, Daniela; Yaya, Issifou; Spire, Bruno; et al.
Abstract : Background: In West Africa, few HIV services target men who have sex with men (MSM). In 2015, the interventional cohort CohMSM started offering a community-based prevention package for MSM. Participants expressed interest in pre-exposure prophylaxis (PrEP) and their eligibility was demonstrated. In 2017, PrEP was added to services already offered as part of a new program, CohMSM-PrEP, which recruited CohMSM participants and new participants. We aimed to determine whether the introduction of PrEP as an additional prevention tool influenced the type of participant signing up for CohMSM-PrEP. Methods: CohMSM-PrEP recruited HIV-negative MSM in community-based clinics in Mali, Cote d'Ivoire, Burkina Faso, and Togo. Quarterly follow-up included free clinical examinations, PrEP, HIV/sexually transmitted infection screening, peer education, condoms, and lubricants. Sociobehavioral data were collected every 3 months using face-to-face questionnaires. Our outcome was participant type: new participants vs CohMSM participants. Logistic regression was performed to identify the factors associated with being a new participant. Results: Of the 524 MSM included in CohMSM-PrEP, 41% were new participants. After adjustment, multivariate analysis showed they were more socioeconomically disadvantaged with financial insecurity, social isolation—including isolation within the MSM community—and riskier sexual practices. Conclusion: The introduction of PrEP as an additional prevention tool and the use of peer-based outreach services over time influenced the type of participant signing up for a community-based HIV prevention cohort in West Africa. Adding these elements to existing interventions in Sub-Saharan Africa could be the key to reaching MSM marginalized from HIV prevention and care programs. Abstract : Supplemental Digital Content is Available in the Text.